Distance and orientation of hydrophones influence the received soundscape in shallow coral reefs - Azofeifa-Solano, Juan Carlos; Erbe, Christine; Tollefsen, Cristina; McCauley, Robert D.; Brooker, Rohan M.; Pygas, Daniel; Parsons, Miles J. G. (Frontiers in Remote Sensing, 2025)
IntroductionAcoustic monitoring and soundscape analysis provide valuable data for the conservation and restoration of underwater habitats. However, before these methods can be widely implemented for management purposes, it is crucial to validate the ecological relevance of different sampling methodologies and quantify potential biases.MethodsWe investigated how the distance and orientation of an acoustic sensor relative to a target habitat influence the received soundscape. Using a spatial array of hydrophones, we recorded sound at different distances (1 m, 2 m, 5 m) and orientations (vertical vs. horizontal) from a shallow coral reef.ResultsHydrophones oriented horizontally toward the reef exhibited the expected decrease in sound levels with increasing distance. In contrast, hydrophones oriented vertically showed an inverse trend, with lower sound pressure levels at closer distances and higher levels further away.DiscussionThese findings indicate that sensor directivity significantly influences the received soundscape, introducing a potential methodological bias within and across acoustic datasets. To improve the accuracy and comparability of acoustic sampling in coastal habitats, sensor beam patterns should be carefully considered in experimental design.